Peran Studi Banding dalam Meningkatkan Kualitas Guru dan Kinerja Sekolah - Purwanto, Muhammad Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Efforts to improve teacher quality can be raised through two sides: 1). The External Side, namely the encouragement from outside that spurs to participate in academic activities or upgrading or the existence of educational institutions that provide opportunities for students to study again; and 2). The internal side is that someone can learn independently to grow in the office. Thus, the figure or figure of a teacher that society expects is a teacher who has the ability and skills to create optimal learning outcomes, has sensitivity in reading the signs of the times, has intellectual insight and is forward-thinking, and is never satisfied with existing knowledge. On him. One of the efforts to improve the teacher quality indicators above is to carry out comparative study activities. Usually, comparative studies are carried out to improve the quality of human resources of a particular institution/agency, where one of the benefits of having a comparative study is to provide enlightenment or inspiration to the driving force personnel from the said institution/institution, to get new enthusiasm in carrying out their duties and functions. From the results of the descriptive study, it is evident that the role of comparative studies in improving teacher quality and school performance is genuine and essential. This is because the comparative study is a learning concept carried out in different locations and environments, which is an activity that schools commonly carry out to improve quality, formulate plans, expand the business, improve systems, determine new policies, and improve laws and regulations. Keywords: Comparative study; Teacher Quality; School Performance.